Social safety nets are crucial to the COVID-19 response: Some lessons to boost their effectiveness - Gilligan, Daniel O. (International Food Policy Research Institute, 2020)
As they try to contain the pandemic, countries must also confront a rise in extreme poverty and the suffering that goes along with it. But they have many tools to combat this problem. Extensive research on social assistance programs provides a firm foundation for approaches to strengthen safety net designs and adapt responses to fit changing circumstances. These actions can improve social safety nets and help to counter some of the worst effects of the COVID-19 pandemic.